Pengaruh Model Pembelajaran Make A Match berbantu Media Kartu terhadap Hasil Belajar Siswa di SMA Negeri 15 Palembang - Rika Silviana Siregar; Depi Pramika; Hendri Gunawan (Bedelau: Journal of Education and Learning, 2024)
This researcher aims to determine the effect of the make a match learning model assisted by card media on the learning outcomes of class X students at SMA Negeri 15 Palembang. The research method is experimental using True Experimental Design post-test only control design. The population of this study were all class X students with a sample of class X.1 and X.7 students using the Simple Random Sampling technique. Data collection techniques are observation and tests. The research results were obtained from the average posttest score from the experimental class of 85 and the control class of 72. From the results of data analysis with normal and homogeneous distribution, data analysis using hypothesis testing obtained a calculated t value of 6,548 > 1,991 t table with the Ha criteria being accepted. It is proven that there is an influence of the make a match learning model assisted by card media on student learning outcomes